Silver(I) and Copper(II) 1,10-Phenanthroline-5,6-dione Complexes as Promising Antivirulence Strategy against Leishmania: Focus on Gp63 (Leishmanolysin) - Simone S. C. Oliveira; Claudyane A. Correia; Vanessa S. Santos; Elaine F. F. da Cunha; Alexandre A. de Castro; Teodorico C. Ramalho; Michael Devereux; Malachy McCann; Marta H. Branquinha; André L. S. Santos (Tropical Medicine and Infectious Disease, 2023)
Leishmaniasis, caused by protozoa of the genus Leishmania, encompasses a group of neglected diseases with diverse clinical and epidemiological manifestations that can be fatal if not adequately and promptly managed/treated. The current chemotherapy options for this disease are expensive, require invasive administration and often lead to severe side effects. In this regard, our research group has previously reported the potent anti-Leishmania activity of two coordination compounds (complexes) derived from 1,10-phenanthroline-5,6-dione (phendione): [Cu(phendione)3].(ClO4)2.4H2O and [Ag(phendione)2].ClO4. The present study aimed to evaluate the effects of these complexes on leishmanolysin (gp63), a virulence factor produced by all Leishmania species that plays multiple functions and is recognized as a potential target for antiparasitic drugs. The results showed that both Ag-phendione (−74.82 kcal/mol) and Cu-phendione (−68.16 kcal/mol) were capable of interacting with the amino acids comprising the active site of the gp63 protein, exhibiting more favorable interaction energies compared to phendione alone (−39.75 kcal/mol) or 1,10-phenanthroline (−45.83 kcal/mol; a classical gp63 inhibitor) as judged by molecular docking assay. The analysis of kinetic parameters using the fluorogenic substrate Z-Phe-Arg-AMC indicated Vmax and apparent Km values of 0.064 µM/s and 14.18 µM, respectively, for the released gp63. The effects of both complexes on gp63 proteolytic activity were consistent with the in silico assay, where Ag-phendione exhibited the highest gp63 inhibition capacity against gp63, with an IC50 value of 2.16 µM and the lowest inhibitory constant value (Ki = 5.13 µM), followed by Cu-phendione (IC50 = 163 µM and Ki = 27.05 µM). Notably, pretreatment of live L. amazonensis promastigotes with the complexes resulted in a significant reduction in the expression of gp63 protein, including the isoforms located on the parasite cell surface. Both complexes markedly decreased the in vitro association indexes between L. amazonensis promastigotes and THP-1 human macrophages; however, this effect was reversed by the addition of soluble gp63 molecules to the interaction medium. Collectively, our findings highlight the potential use of these potent complexes in antivirulence therapy against Leishmania, offering new insights for the development of effective treatments for leishmaniasis.